URGENSI AMANDEMEN TERBATAS POKOK POKOK HALUAN NEGARA (PPHN) - Ni Made Anggia Paramesthi Fajar (Jurnal Yustitia, 2021)
Abstrak Reformasi membawa misi besar terhadap amandemen UUD 1945. Sebagai kontitusi dalam menjalankan pemerintahan dan bernegara UUD 1945 di rasa sangat penting peranannya untuk menjadi acuan dalam merumuskan suatu peraturan perundang-undangan. Amandemen pun telah berhasil dilakukan sebanyak 4 kali, namun dalam perjalanan amandemen tersebut masih di asa banyak kekurangan dan kurang sempurna dalam pemebentukan pasal-pasalnya. Kendatipun perubahan sudah dilaksanakan dan telah melahirkan system ketatanegaraan dengan wajah baru utuk Indonesia, wacana amandemen untuk penyempurnaan aturan-atuan dalam UUD masih saja terus di usahakan. Wacana amandemen ke 5 kembali muncul di permukaan dengan dengan gaung amandemen terbatas pada PPHN, wacana ingin menghidupkan GBHN dengan gaya baru inipun mulai menuai problrmatika dalam masyarakat. Kata kunci : Kontitusi, Amandemen , PPHN Abstract Reform lead a great mission for the amendment of the 1945 Constitution. As a constitution in running the government and as a state, the 1945 Constitution is considered very important to serve as a reference in formulating a statutory regulation. The amendments have also been successfully carried out 4 times, but in the course of the amendments there are still many shortcomings and imperfections in the formation of the articles. Even though the changes have been implemented and have given birth to a constitutional system with a new face for Indonesia, the discourse on amendments to improve the rules in the Constitution is still being worked on. The discourse of the 5th amendment re-emerged on the surface with the echo of the limited amendment to the PPHN, the discourse of wanting to revive the GBHN with this new style has begun to reap problems in society. Key Word : Constitution ,Amandement , PPHN